Cytokine and Haptoglobin Profiles From Shipping Through Sickness and Recovery in Metaphylaxis- or Un-Treated Cattle - Chitko-McKown, Carol G.; Bennett, Gary L.; Kuehn, Larry A.; DeDonder, Keith D.; Apley, Michael D.; Harhay, Gregory P.; Clawson, Michael L.; Workman, Aspen M.; White, Bradley J.; Larson, Robert L.; Capik, Sarah F.; Lubbers, Brian V. (Frontiers in Veterinary Science, 2021)
Fifty-six head of cattle, 28 animals with bovine respiratory disease complex (BRDC), and 28 healthy animals that were matched by treatment, state of origin, day, and interactions among these variables, were identified from a population of 180 animals (60 each purchased at three sale barns located in MO, TN, and KY) enrolled in a study comparing animals receiving metaphylaxis to saline-treated controls. Cattle were transported to a feedlot in KS and assigned to treatment group. Blood samples were collected at Day 0 (at sale barn), Day 1, Day 9, and Day 28 (at KS feedlot), and transported to the US Meat Animal Research Center in Clay Center, NE where plasma was harvested and stored at -80C until assayed for the cytokines IFN- IL-1, IL-6, and TNF-, and the acute stress protein haptoglobin (HPT). Our objectives were to determine if cytokine and haptoglobin profiles differed between control and metaphylaxis treatment groups over time, and if profiles differed between animals presenting with BRDC and those that remained healthy. There was no difference between the treated animals and their non-treated counterparts for any of the analytes measured. State of origin tended to affect TNF- concentration. Differences for all analytes changed over days, and on specific days was associated with state of origin and treatment. The Treatment by Day by Case interaction was significant for HPT. Concentrations of IFN-, IL-1 and IL-6 were higher in healthy cattle than their matched BRDC counterparts, but concentrations of TNF- and Haptoglobin were higher in animals with BRDC.